KEPEMIMPINAN VISIONER KEPALA MASDRASAH ALIYAH DALAM MENINGKATKAN MUTU LEMBAGA PENDIDIKAN ISLAM - Said, Muhammad; Amin, Surahman; Abdillah, Fardan (Pascasarjana IAIN Sorong, 2023)
The aims of this scientific research are: 1) To analyze the Visionary Leadership Role of the Head of Madrasah Aliyah Imam Adil, Raja Ampat Regency in Improving the Quality of Islamic Educational Institutions. 2) To analyze the Visionary Leadership Strategy of the Head of Madrasah Aliyah IMadrasah Aliyahm Adil, Raja Ampat Regency in Improving the Quality of Islamic Educational Institutions. This research uses a descriptive qualitative research type located at the Imam Adil Madrasah Aliyah School, Raja Ampat Regency, West Papua Province. The approach in this research uses a qualitative descriptive approach. The data sources in this research are primary and secondary data sources. The data collection methods used were observation, interviews and documentation. Analysis of this research data through data reduction, data presentation and drawing conclusions. The results of the research show that: 1) The Head of Madrasah Aliyah Imam Adil Raja Ampat Regency reflects visionary leadership in Madrasah Aliyah Imam Adil. The leader plays a role as a direction maker, which means providing clarity to his followers about the ways or efforts that must be taken, the steps of the Head of Madrasah Aliyah Imam Adil continues to pay attention to effective and efficient goals. The Head of Madrasah Aliyah Imam Adil Raja Ampat Regency, in carrying out his leadership, has tried to focus on the vision and mission created, building good relationships at both internal and external levels. 2) The Head of Madrasah Aliyah Imam Adil Raja Ampat Regency seeks to carry out a visionary leadership role as an agent of change with new programs from previous programs. 3) The efforts made by the Head of Madrasah Aliyah Imam Adil Raja Ampat Regency to improve quality are to create an effective learning process, conduct effective evaluations and carry out continuous improvements, build character, carry out constructive guidance